Preaching Ezra–Nehemiah’s Religious Minority-Group Narratives for Post-Christendom Congregations - Matzal, Stefan C. (My University, 2024)
As North America moves from Christendom to post-Christendom, the church needs resources that foster spiritual strength. Ezra–Nehemiah has a role to play here because the original audience was a religious minority-group, as is the evangelical church in North America. What exactly, however, are the challenges that Christians experience today in their interface with the non-Christian majority culture? This dissertation seeks to answer that question for the benefit of contemporary preachers of Ezra–Nehemiah. This research project proceeded in three phases. First, literature-based research was used to prepare three sermons from Ezra–Nehemiah. Chapter 2 describes narrative analysis of Ezra 4–6; Neh 1–6; and Neh 9–10. For the sake of the development of Christian sermons, Chapter 3 draws links from these texts to the New Testament. Chapter 4 describes the process of developing sermons, one from each of the three passages. In the second phase of this project, I preached these sermons at eight different churches across the Northeast US and Eastern Canada. The preached sermon then functioned as a springboard for discussion in a focus group interview, one per church, populated by people who had listened to the sermon. I asked congregants in what ways they found their interface with the non-Christian world to be challenging. Chapter 5 presents my analysis of the focus group data. In the third phase of the project, described in Chapters 6 and 7, I integrated the exegesis of Ezra–Nehemiah and the focus group analysis in order to derive recommendations for pastors regarding preaching biblical minority-group literature to Christians living in the post-Christendom West. One significant conclusion is a call for fearlessness and courage, derived from a robust personal relationship with the God who makes himself known in Christ and by the Spirit.
Keywords: Preaching; post-Christendom